Affirmation of Student Identity Facing the Challenges of Islamic Education in the Era of Society 5.0 - Hastiani, Hastiani; Atika, Amelia; Rustam, Rustam; Naser, Muhammad Nikman; Rahmi, Nurul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2022)
This study aims to affirm students' self-identity through the implementation of biblio-counseling charged with local wisdom in the context of Islamic education. Self-identity reflects who the student is with the regional cultural identity that belongs to the root of the national identity. The identity crisis experienced by students during the development of the current era of society is a challenge for the world of education. The shift in local values in today's life, if not given treatment, will provide an opportunity for students to lose their identity. One alternative solution is by instilling the values of local wisdom as a native force of the region to form student identity. This research method uses a qualitative approach of the hermeneutic type. The purpose of composed hermeneutics is to search for the meaning behind meaning, carrying out a deep interpretation of the process of intersubjectivity. Several high school students in East Pontianak became the setting for biblio-counseling research which was positioned as an affirmation of their identity. Biblio-counseling contains the values of local wisdom of Malay ethnicity and stories that bring students to the situation and conditions that are being read. Students reflect and plan for productive new behavior changes. Students can have broad or global thinking but still, behave and have manners that are under eastern culture.